Vernuwe Die Psigologie: Doen Dit Net Wetenskaplik - Louw, Gabriel (PINS-Psychology in Society, 2026)
RENEW PSYCHOLOGY: ONLY DO IT SCIENTIFICALLY. The promulgation of Act 5 of 1974 succeeded in elevating the South African psychologist from an ancillary mental health practitioner to the status of an independent, self-sufficient mental health practitioner. It has emerged in practice, however, that there are certain professional anomalies which limit psychology. Looked at critically, it would appear as if South African psychology is manifesting symptoms of professional limitation and enclosure. Central to this problem is an urgent need for an adjusted or new professional, curricular and control model. It is clear that the psychologist has come to confront an inevitable reform initiative in his/her profession. S/he can no longer have resort simply to the subjective, contingent and autocratic decisions of self-appointed and uninformed individuals and/or sub-groups in psychology. Only democratic participation of all the determiners (consumers, practitioners, training agencies and the state) in a professional model, system and curriculum can possibly ensure the establishment of an efficient and relevant mental health practitioner for a new South Africa.